Mitigating the Risks of Resource Extraction for Industrial Actors and Northern Indigenous Peoples - Lerner, Alexis Monique; Koshurina, Victoria; Chistanova, Olga; Wheeler, Angela (Arctic Review on Law and Politics, 2017)
A collaborative relationship between native peoples and industrial corporations–two actors that value resource-rich land–is of vital importance for both the United States and the Russian Federation. A strong partnership between industrial and indigenous actors can help to ensure not only the stability of extractive projects, but also the protection of indigenous groups from the potentially existential threats associated with territorial loss. Cooperation between these two parties gains urgency as extractive corporations begin to explore the Arctic, a region of the world already home to over two dozen unique indigenous communities. In both the United States and the Russian Federation, there are legal precedents for negotiations regarding indigenous rights, natural resources, and the fuel-energy complex. Even so, parties involved in the extractive process frequently stray from these national and international legal guidelines. Our paper seeks to answer the question: why might rational actors–here, indigenous and industrial communities that are motivated by their preferences–fail to cooperate on extractive projects, even when robust collaborative agreements benefit all sides? We suggest that the explanation is twofold: first, indigenous land rights lack the consistency which may give indigenous communities control over their resources and cultural preservation; and second, a neutral and objective third-party mediator–whether in the form of a state or an international body–is often silent in, or absent from, the negotiation process, thereby undermining its authority to ensure fair and reasonable deliberations. Our findings can offer important insights for community-corporate relations, not only in the Arctic, but worldwide. (Published: May 2017) Citation: A.M. Lerner et al. “Mitigating the Risks of Resource Extraction for Industrial Actors and Northern Indigenous Peoples.” Arctic Review on Law and Politics, Vol. 8, 2017, pp. 23–51. http://dx.doi.org/10.23865/arctic.v8.659